Implementation of Laplace Transform based Cryptography on Reconfigurable Hardware - Sastry, K.R.K. (International Journal of Advanced Science and Technology, 2020)
Laplace transform find applications to solve Boundary value problems, linear nonlinear differential equations, simplify very complex problems in the area of stability and control systems, power systems.  Laplace transform also useful in cyber security applications such as Mobile, Network, Information, Security,  e mail and Firewall.  Laplace transform (L) and Inverse Laplace transform ( L-1  ) are Linear Transformations. In this paper we discuss the Laplace Transform based encryption and Inverse Laplace transform based decryption for the given data.